The urbanization and growth of Malaysia: case study of Iskandar region - Yasin, Muhammad Yazrin; Abdullah, Jamalunlaili; Mohd Yusof, Mariney; Hj. Mohd. Noor, Norzailawati (International Scientific Invention Journals, 2021)
This paper discusses the process of economic growth and urbanization in Malaysia, the contribution of Johor in the nation’s growth and the development of Iskandar Malaysia. First, we explore the range of institutions that engage in urban and regional planning at various level and their respective statutory development plan. Next, we present the contextual of the south Johor particularly Iskandar region and the new administrative of Iskandar Puteri. The development of Iskandar region is intended to benefit all in south Johor and by coordinating the efforts of various Government agencies, Iskandar Regional Development Authority (IRDA) is helping locals share the benefits of economic growth. Afterwards, we evaluate some issues that have arisen with regard to the physical development and the statutory development plans in Johor and Iskandar region on urbanization and urban growth pattern. From the analysis, we identified that among issues aroused are the absence of urban growth boundary within Iskandar region; land use change and agricultural land encroachment; low density and mixed-use development and environmental change and degradation.